Association between 5α-reductase inhibitors therapy and incidence, cancer-specific mortality, and progression of prostate cancer: evidence from a meta-analysis - Lian-Min Luo (Asian Journal of Andrology, 2020)
5α-reductase inhibitors (5-ARI) are widely employed for the treatment of benign prostatic hyperplasia. It has been noted that 5-ARI exhibit the potential to attenuate the risk of prostate cancer, but consistent agreement has not been achieved. Moreover, the effect of 5-ARI on cancer-specific mortality and progression of prostate cancer remains unclear. Therefore, the goal of the current meta-analysis was to elucidate the impact of 5-ARI on the incidence and progression of prostate cancer. We searched for all studies assessing the effect of 5-ARI on risk of prostate cancer in PubMed, Embase, Medline, and Cochrane Library databases. Pooled relative risk (RR) and corresponding 95% confidence intervals (CIs) were accepted to evaluate the association between 5-ARI and the risk of prostate cancer. Synthetic results implied that subjects who accepted 5-ARI compared with the placebo group experienced a distinctly weakened overall incidence of prostate cancer (RR = 0.74; 95% CI: 0.66–0.82; P < 0.001). Subgroup analyses further revealed that 5-ARI reduction of the incidence of prostate cancer was limited to low-grade (Gleason score 2–6; RR = 0.68; 95% CI: 0.57–0.81; P < 0.001) and intermediate-grade tumors (Gleason score 7; RR = 0.81; 95% CI: 0.67–0.97; P = 0.023), but not high-grade tumors (Gleason score >7; RR = 1.19; 95% CI: 0.98–1.43; P = 0.069). The results also showed that 5-ARI treatment did not significantly alter prostate cancer-specific mortality (RR = 1.0; 95% CI: 0.95–1.05; P = 0.916). In addition, it was worth noting that 5-ARI treatment acted in a protective role that presented a dramatic benefit to delay the progression of low-risk tumors (RR = 0.58; 95% CI: 0.43–0.78; P < 0.001).